Vereiste lugsnelheidsprofiele vir newelblasertoerusting in boorde - Ras, Marthinus C. D.(Marthinus Christoffel David) (Stellenbosch : Stellenbosch University, 2012)
Tesis (M. Ing.) -- Universiteit van Stellenbosch, 1991.